L-shaped association of dietary inflammatory index (DII) and chronic diarrhea: results from NHANES 2005–2010 - Qing Zhao; Yue Xu; Xiangrui Li; Xiaotian Chen (BMC Public Health)
Abstract Background Since diet is a known modulator of inflammation, the Dietary Inflammatory Index (DII), which quantifies the inflammatory potential of an individual’s diet, becomes a significant parameter to consider. Chronic diarrhea is commonly linked to inflammatory processes within the gut. Thus, this study aimed to explore the potential link between DII and chronic diarrhea. Methods This research utilized data from the National Health and Nutrition Examination Survey (NHANES) 2005–2010. The DII was calculated according to the average intake of 28 nutrients using information gathered from two 24-hour recall interviews. The Bristol Stool Form Scale (BSFS) was adopted to describe chronic diarrhea, identifying stool Type 6 and Type 7. Multivariate logistic regression models examined the causal connection between DII and chronic diarrhea. Additionally, subgroup analyses and interaction tests were conducted. Results The study encompassed 11,219 adults, among whom 7.45% reported chronic diarrhea. Initially, multivariate logistic regression analysis revealed a positive association between DII and chronic diarrhea. Nevertheless, this connection lost statistical significance (OR = 1.00; 95% CI, 0.96–1.05; P = 0.8501) after adjusting for all confounding variables. Stratified by sex, the analysis revealed a notable rise in the risk of chronic diarrhea with increasing DII among female participants (all P for trend < 0.05). This tendency remained constant even after full adjustment (P for trend = 0.0192), whereas no significant association was noted in males (all P for trend > 0.05). Furthermore, an L-shaped association emerged between DII and chronic diarrhea, with an inflection point of -1.34. In the population with DII scores below -1.34, each unit increase in DII correlated with a 27% reduction in the probability of chronic diarrhea (OR = 0.73; 95% CI, 0.57–0.93), whereas in the population with DII scores above -1.34, the risk increased by 4% (OR = 1.04; 95% CI, 0.98–1.10). Merely, the gender interaction was shown to be statistically significant based on subgroup analyses and interaction tests. Conclusions A favorable association between DII and chronic diarrhea exists in adults in the United States. Nevertheless, additional long-term prospective studies are required to confirm and solidify those findings.